Agile development of open educational resources - Arimoto, Mauricio Massaru (2016)
Over the years, the rapid advance of the computer and communication technologies has significantly changed the way in which the society communicates and conducts business. Similarly, changes have occurred in the way in which educational resources are designed, developed and made available to learners. Following this trend, the development and adoption of Open Educational Resources (OERs) has been gaining more supporters across the world, as a means to expand access to knowledge and improve education. Indeed, the free and open distribution of educational resources helps disseminate knowledge, facilitates access to information and promotes the democratisation of access to education, benefiting society as a whole. While OERs can bring benefits to, and impact on education, there are still challenges to their widespread production and adoption. One of the challenges faced by developers (including educators and practitioners) of OERs is to produce quality and relevant learning materials, capable of being reused and adapted in different contexts and learning situations. Also, there is a need for mechanisms that provide higher productivity of the development process and quality of the resulting OERs. This work aims to investigate the development of OERs and establish flexible approaches to effectively support the design and creation of these resources. In this context, an agile method for the development and sharing of OERs, named AM-OER, was established. It is grounded on practices of Software Engineering and on practices of Learning Design. Such practices are embedded in the development of OERs aiming at improving quality and facilitating reuse and adaptation. The ultimate aim of AM-OER is to support the development of quality OERs, able to motivate and guide learners in the process of knowledge construction. Preliminary empirical assessments were conducted to validate AM-OER through its application in the design and creation of courses in the free and open source software development and software testing domain. The results obtained so far have shown that the method is feasible and effective for the design and creation of OERs.